Central and lateral neck involvement in papillary thyroid carcinoma patients with or without thyroid capsular invasion: A multi-center analysis - Yang, Zheyu; Heng, Yu; Zhou, Jian; Tao, Lei; Cai, Wei (Frontiers in Endocrinology, 2023)
Purposes To quantitatively predict the probability of cervical lymph node metastasis for papillary thyroid carcinomas (PTC) patients with or without thyroid capsular invasion (TCI), to guide the decision-making of management strategies for neck regions. Methods A total of 998 PTC patients from three medical centers were retrospectively analyzed. Results Patients with positive TCI (TCI group) exhibited higher risks for both CLNM and LLNM than those with negative TCI (no-TCI group). Patients receiving lateral lymph node dissection showed significantly higher incidence of relatively severe postoperative complications. For no-TCI group, factors including age less than 55 years old, male, the presence of bilateral disease and multifocality, and maximum tumor diameter (MTD)>=0.5cm were confirmed to be independent risk factors for CLNM, while the presence of bilateral disease and ipsilateral nodular goiter (iNG), and maximum positive CLN diameter (MCLND)>1.0cm independent factors for LLNM. Independent risk factors of LLNM for patients within the TCI group included MCLND>1.0cm, positive CLN number>=3, and the presence of iNG. Predictive models of CLNM and LLNM were established based on the aforementioned risk factors for patients within no-TCI and TCI groups. A meticulous and comprehensive risk stratification flow chart was established for a more accurate evaluation of central neck involvement including both CLNM and LLNM risk in PTC patients. Conclusions A meticulous and comprehensive stratification flow chart for PTC patients for quantitatively evaluating both CLNM and LLNM was constructed.